Effects Of Green Farming Practices/Environmentally Friendly Practices On Small Scale Agricultural Production In Kenya, A Case Study In Siaya County. (Global Journal of Management and Business Research, 2024)
Smallholder farmers, who face sustainability challenges due to reliance on conventional farming practices, dominate Kenya's agricultural sector. This study investigated the impact of adopting green farming practices on the agricultural productivity, economic viability and environmental sustainability of small-scale farms in Siaya County. A mixed methods approach combined analysis of published secondary data with primary data collected through questionnaires administered to a sample of 150 smallholder farmers in Siaya. The questionnaires utilized descriptive analysis to assess the adoption rate of different green farming techniques over the past five years and used both qualitative and quantitative analysis to evaluate outcomes related to agricultural yields, income generation, social welfare, and conservation goals. Quantitative data was analyzed statistically in Microsoft Excel using tables, graphs and charts. Specific statistical tests used included ANOVA analysis to determine any associations and differences between groups, and regression analysis to examine correlations between green farming adoption and productivity, financial and sustainability indicators. The study tested hypotheses on the relationship between implementing environmentally friendly techniques and productivity levels, economic returns, and ecological impacts.